A lab for undergraduate control engineering education equipped with industrial distributed control systems. Issue 2 (6th November 2015) - Dittmar, Rainer; Kahlcke, Thomas
ABSTRACT: The paper demonstrates how a set of pilot plant air blower/heater systems connected to modern industrial distributed control systems (DCS) are used in different control engineering laboratories for the undergraduate level. Student's tasks include the identification of static and dynamic process models and the tuning and commissioning of Proportional‐Integral‐Derivative (PID) control loops, as well as the utilization of commercial tools for DCS engineering. Using the same pilot plants, DCS and scientific computing environment in different courses lowers the costs, allows the reutilization of results and enables an efficient lab organization. It also supports the process of learning the inner context of different control engineering related subjects. The use of industrial‐scale equipment and commercial software helps students to easily integrate in their later teams and to avoid the "reality shock" when making the transition from academia to industry. © 2015 Wiley Periodicals, Inc. Comput Appl Eng Educ 24:288–296, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21708